Dynamics of the Ebrié Lagoon from 1986 to 2017 (Southern of Ivory Coast): contribution of Remote sensing and GIS (International Journal of Engineering and Computer Science, 2018)
Situated in the South of Ivory Coast. Lagoon Ebrié presents an interest for tourist and socioeconomic. However, it has been subjected to strong anthropogenic pressure, in the case of the work of development and the construction of habitats on its borders causing silting and filling the lagoon Bays. The objective of this study is to evaluate the dynamics of the bays of the water of the city of Abidjan from 1986 to 2017 in order to contribute to a better management of these environments. The study was realized thanks to the use of satellite data and thanks to the observations of ground. She based on the diachronic analysis of the years Landsat satellite images 1986, 2000, 2015 and 2017. The results showed a negative evolution of whole of the surface of the water of the Ébrié Lagoon which went from 8742 hectares in 1986 to 8393 hectares in 2017 is a regression of 4% of the surface of the water. Besides, the study revealed that the determining factor of the loss of the surfaces of the lagoon water is the anthropogenic pressure.